Building Consumer Purchasing Decisions At Fast-Food Restaurants And Cafes In Tegal - Sari Wiyanti; Gunistyo Gunistyo (Enrichment : Journal of Management, 2022)
This research in Indonesian, especialy in Tegal because Investment growth in Tegal is very high, this can be seen by the number of foreign companies, hotels, malls, fast food restaurants and cafes in Tegal. The rise of fast food restaurants and cafes in Tegal is due to the high level of public consumption. In 2021, it was recorded at https://jateng.bps.go.id as many as 135 fast food restaurants and cafes in Tegal. The product served are varied, ranging from authentic Indonesian culinary dishes to foreign dishes. This study analyzes the factors that are able to build consumer purchasing decisions in consuming food at fast food restaurants and cafes in Tegal, namely the impression of quality, brand awareness, and brand loyalty. The sampling technique in this study uses purposive sampling. The data used in this study is primary data, which was obtained by conducting surveys and distributing questionnaires to 100 respondents, namely visitors to fast food restaurants and cafes in Tegal. The data obtained will be analyzed using multiple linear regression analysis. The analytical tool used to process the data is SPSS 22. The results of the simultaneous test (Test F) from this study is the value of sig 0.00 < 0.05 which means the hypothesis is "proven or accepted", this proves that Perceived Quality, Brand Awareness, and Brand Loyalty have an effect on building Consumer Purchasing Decisions in Fast Food Restaurants and cafes in Tegal.